Analysis and Optimization of FEAD Belt Noise based on Crankshaft Torsion Vibration Damper - Jun Zhang; Yanchao Zhang; Chuanzhi Ai (Jixie chuandong, 2022)
Belt drive has been widely used in front end auxiliary system of vehicle internal combustion engine. The vibration and noise of belt have drawn more and more attention，which directly affects the safe and comfortable driving experience of market customers. In order to solve the belt noise problem，the abnormal noise of the engine bay during the acceleration of a compact SUV model is taken as an example to systematically carry out the identification and investigation of the belt noise. The potential mechanism of the belt transverse vibration and noise is expounded. By optimizing the dynamic characteristics of the crankshaft damper TVD，the torsional vibration excitation of the accessory belt train is reduced. Then，the belt abnormal noise is eliminated and the dynamic sound quality of the vehicle is improved. The paper provides a new engineering development idea for solving similar belt noise problems.